(untitled) (Лучшие интеллектуальные исследования, 2025)
As Uzbekistan strengthens its ties with the global community, proficiency in the English language has become a national priority. This focus begins with the youngest learners in the nation’s primary schools. Moving beyond traditional rote memorization, educators are discovering that a dynamic, culturally-responsive approach is the key to successfully teaching English vocabulary. This article explores effective, evidence-based strategies tailored to the unique linguistic and cultural context of young Uzbek learners, advocating for a blend of global best practices and local integration.